Cohort profile: China National Human Biomonitoring (CNHBM)—A nationally representative, prospective cohort in Chinese population. (January 2021) - Cao, Zhaojin; Lin, Shaobin; Zhao, Feng; Lv, Yuebin; Qu, Yingli; Hu, Xiaojian; Yu, Shicheng; Song, Shixun; Lu, Yifu; Yan, Huifang; Liu, Yingchun; Ding, Liang; et al.
Highlights: A total of 21, 746 participants were included using multi-stage stratified sampling in China NHBP. Information on comprehensive epidemiological, biological and internal exposure of environmental chemicals was collected. China NHBP created the first large, nationally-representative cohort of Chinese population for human biomonitoring. Abstract: Objective: Globally, developed countries such as the United States, Canada, Germany, Korea, have carried out long-term and systematic biomonitoring programs for environmental chemicals in their populations. The China National Human Biomonitoring (CNHBM) was to document the extent of human exposure to a wide array of environmental chemicals, to understand exposure profiles, magnitude and ongoing trends in exposure in the general Chinese population, and to establish a national biorepository. Methods: CNHBM adopted three-stage sampling method to obtain a nationally representative sample of the population. A total of 21, 888 participants who were permanent residents in 31 provinces were designed to interviewed in this national biomonitoring (152 monitoring sites × 3 survey units × 2 sexes × 6 age groups × 4 persons = 21, 888 persons) in 2017–2018. Unlike the US National Health and Nutrition Examination Survey, the CNHBM will follow the same participants in subsequent cycles allowing for dynamic, longitudinal data sets for epidemiologic follow-up. Each survey cycle of CNHBM will last 2 years and each subsequent cycle will occur 3 years after the prior cycle's completion. Results: In 2017–2018, the CNHBM created a large cohort of Chinese citizens that included districts/counties questionnaire, community questionnaire collecting information on villages/communities, individual questionnaire, household questionnaire, comprehensive medical examination, and collection of blood and urine samples for measurement of clinical and exposure biomarkers. A total of 21, 746 participants were finally included in CNHBM, accounting for 99.4% of the designed sample size; and 152 PSUs questionnaires, 454 community questionnaires, 21, 619 family questionnaires, 21, 712 cases of medical examinations, 21, 700 individual questionnaires, 21, 701 blood samples and 21, 704 urine samples were collected, respectively. Planned analyses of blood and urine samples were to measure both inorganic and organic chemicals, including 13 heavy metals and metalloids, 18 poly- and per-fluorinated alkyl substances, 12 phthalate metabolites, 9 polycyclic aromatic hydrocarbons metabolites, 4 environmental alkylated phenols, and 2 benzene metabolites. Conclusions: CNHBM established the first nationally representative, prospective cohort in the Chinese population to understand the baseline and trend of internal exposure of environmental chemicals in general population, and to understand environmental toxicity.